Assessing Youth Unemployment Rate in Malaysia using Multiple Linear Regression / Tan Vyn Ni ... [et al.] - Tan, Vyn Ni; Md Yusof, Zahayu; Misiran, Masnita; Supadi, Siti Suzlin (Unit Penerbitan UiTM Kelantan, 2021)
This study investigated the relationship between urbanization, inflation, gross domestic product and foreign direct investment towards youth unemployment in Malaysia. As youth unemployment has been increasing over the past decade, it is therefore crucial to decide which variables are the most critical in affecting Malaysia's youth unemployment rate as to ensure sustainable economic growth in the country. Data was obtained from Department of Statistics Malaysia and World Bank websites. Descriptive and multiple linear regressions were used in this study. The outcome revealed that foreign direct investment and gross domestic product growth are significant factors, while urbanization and inflation showed insignificant relationship towards the contribution to the youth unemployment rate.